Is it Possible to be Better Off Dead? An Epicurean Analysis of Physician-Assisted Suicide - Pavelich, Andrew (Conatus - Journal of Philosophy, 2020)
Epicurus wrote that death cannot be bad for a person who dies, since when someone dies they no longer exist to be the subject of harm. But his conclusion also applies in the converse: Death cannot be good for someone, since after their death they will not exist to be the subject of benefit. This conclusion is troubling when it is brought to bear on the question of physician assisted suicide. If Epicurus is right, as I think he is, then it means that even when someone is dying of a long and painful illness, we cannot say that they would be better off dead. I defend this conclusion by first presenting Epicurus’s argument, and defending it against some of its more important contemporary critics. I then re-examine the conclusion that someone cannot be better off dead by looking at the issue of mercy killing and euthanasia. Drawing on the work of philosophers who examine the ethics of animal euthanasia, I argue that killing someone who is suffering severe agony can be good, but it cannot be good for the person who suffers – it is just good in itself. This, I think, is why we have the intuitions that we do around physician assisted suicide: we are mistaken about the idea that someone can be better off dead, but we can be correct in thinking that sometimes someone’s death is good.